The Metabolic and Proliferative State of Vascular Adventitial Fibroblasts in Pulmonary Hypertension is Regulated through a MiR-124/PTBP1/PKM Axis - Zhang, Hui; Wang, Daren; Li, Min; Plecitá-Hlavatá, Lydie; D’Alessandro, Angelo; Tauber, Jan; Riddle, Suzette; Kumar, Sushil; Flockton, Amanda; McKeon, B. Alexandre; Frid, Maria G.; Reisz, Julie A.; et al. (Circulation (New York, N.Y.), 2017)
BACKGROUND—An emerging 'metabolic theory' of pulmonary hypertension (PH) suggests that cellular and mitochondrial metabolic dysfunction underlies the pathology of this disease. We and others have previously demonstrated the existence of hyper-proliferative, apoptosis-resistant, pro-inflammatory adventitial fibroblasts from human and bovine hypertensive pulmonary arterial walls (PH-Fibs) exhibit constitutive reprogramming of glycolytic and mitochondrial metabolism, accompanied by an increased ratio of glucose catabolism through glycolysis versus the TCA cycle. However, the mechanisms responsible for these metabolic alterations in PH-Fibs remain unknown. We hypothesized that, in PH-Fibs, miR-124 regulates polypyrimidine tract binding protein 1 (PTBP1) expression to control alternative splicing of pyruvate kinase muscle isoforms 1 and 2 (PKM1 and PKM2) resulting in an increased PKM2/PKM1 ratio which promotes glycolysis and proliferation even in aerobic environments. METHODS—Pulmonary adventitial fibroblasts were isolated from calves and humans with severe PH (PH-Fibs) and from normal subjects (CO-Fibs). PTBP1 gene knockdown was achieved via PTBP1-siRNA, restoration of miR-124 was performed with miR-124 mimic. TEPP-46 and Shikonin were utilized to manipulate PKM2 glycolytic function. HDACi were used to treat cells. Metabolic products were determined by Mass spectrometry-based metabolomics analyses (UHPLC-MS), and mitochondrial function was analyzed by confocal microscopy and spectrofluorometry. RESULTS—We detected an increased PKM2/PKM1 ratio in PH-Fibs compared to CO-Fibs. PKM2 inhibition reversed the glycolytic status of PH-Fibs, decreased their cell proliferation and attenuated macrophage IL-1β expression. Further, normalizing the PKM2/PKM1 ratio in PH-Fibs by miR-124 overexpression or PTBP1 knockdown reversed the glycolytic phenotype (decreased the production of glycolytic intermediates and byproducts, i.e. lactate), rescued mitochondrial reprogramming and decreased cell proliferation. Pharmacological manipulation of PKM2 activity with TEPP-46 and Shikonin, or treatment with histone deacetylase inhibitors (HDACi), produced similar results. CONCLUSIONS—In PH, miR-124, through the alternative splicing factor PTBP1, regulates the PKM2/PKM1 ratio, the overall metabolic, proliferative and inflammatory state of cells. This PH phenotype can be rescued with interventions at various levels of the metabolic cascade. These findings suggest a more integrated view of vascular cell metabolism, which may open unique therapeutic prospects in targeting the dynamic glycolytic and mitochondrial interactions and between mesenchymal inflammatory cells in PH.